Benefits of Fasting Abbreviation with Carbohydrates and Omega-3 Infusion During CABG: a Double-Blind Controlled Randomized Trial - Feguri,Gibran Roder (2019)
Abstract Objective: To assess postoperative clinical data considering the association of preoperative fasting with carbohydrate (CHO) loading and intraoperative infusion of omega-3 polyunsaturated fatty acids (ω-3 PUFA). Methods: 57 patients undergoing coronary artery bypass grafting (CABG) were randomly assigned to receive 12.5% maltodextrin (200 mL, 2 h before anesthesia), (CHO, n=14); water (200 mL, 2 h before anesthesia), (control, n=14); 12.5% maltodextrin (200 mL, 2 h before anesthesia) plus intraoperative infusion of ω-3 PUFA (0.2 g/kg), (CHO+W3, n=15); or water (200 mL, 2 h before anesthesia) plus intraoperative infusion of ω-3 PUFA (0.2 g/kg), (W3, n=14). The need for vasoactive drugs was analyzed, in addition to postoperative inflammation and metabolic control. Results: There were two deaths (3.5%). Patients in CHO groups presented a lower incidence of hospital infection (RR=0.29, 95% CI 0.09-0.94; P=0.023), needed fewer vasoactive drugs during surgery and ICU stay (P<0.05); and had better blood glucose levels in the first six hours of recovery (P=0.015), requiring less exogenous insulin (P=0.018). Incidence of postoperative atrial fibrillation (POAF) varied significantly among groups (P=0.009). Subjects who receive ω-3 PUFA groups had fewer occurrences of POAF (RR=4.83, 95% CI 1.56-15.02; P=0.001). Patients in the W3 group had lower ultrasensitive-CRP levels at 36 h postoperatively (P=0.008). Interleukin-10 levels varied among groups (P=0.013), with the highest levels observed in the postoperative of patients who received intraoperative infusion of ω-3 PUFA (P=0.049). Conclusion: Fasting abbreviation with carbohydrate loading and intraoperative infusion of ω-3 PUFA is safe and supports faster postoperative recovery in patients undergoing on-pump CABG.